Measuring Student Adoption of Digital Platforms for Distance Education among University Students in Malaysia - Abu Bakar, Nashirah; Abdul Aziz, Ibrahim; Md Hussain, Muhammad Nasri; Ishak, Nor Syahidah (Asian Scholars Network, 2023)
A discipline of education known as distance education or distance learning focuses on the pedagogy, technology, and instructional system design that successfully delivers education to students who are not physically "on-site" to get their education. Instead, they can exchange written or electronic materials asynchronously (at times of their choice) or synchronously (in real-time) using technology. A hybrid or blended course or program combines online learning with on-site attendance for any reason, including completing exams. Since then, colleges have used remote learning in conjunction with modern information technology to expand their market outside their immediate surroundings. Therefore, this study was performed to measure student adoption of digital platforms for distance education among university students in Malaysia. This study uses primary data collection with self-administered questionnaire development. The sample size is 100 students which represents the population of students that registered for distance education programs. The underpinning theory for this study is the Information System Success Model (ISSM). There are three independent variables: information quality, system quality, and service quality. According to the findings, information quality, system quality, and service quality, all have a positive and substantial impact on the intention to adopt digital platforms for distance education. This work will benefit academics, decision-makers, and system designers by providing useful implications for generating appropriate methods and building successful and practical ways to develop the online learning system of distance education